Pseudotumor Cerebri: Epidemiology - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The population-based incidence rates and clinical features of idiopathic intracranial hypertension (IIH) are reported from the Mayo Clinic.